Studi Kelayakan Sungai Cidanau Kabupaten Serang Banten untuk Kebutuhan Sumber Air Baku Kecamatan Padarincang - Ade Ariesmayana; Frebhika Sri Puji Pangesti; Anis Khaerunnisa (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Cidanau River water is one of the important facilities for the people of Padarincang District. People use the river flow for their daily needs. Along its course there are non-densely populated settlements, where residents dump domestic waste into rivers. The purpose of this study is to analyze river water quality, the amount of raw water needs and the feasibility of the Cidanau River. The study used quantitative methods in the form of water sampling, population growth projections and river water feasibility by analyzing the water quality of the Cidanau River with the Pollution Index (IP) method. The results of the pollution index can be concluded that the Cidanau River meets quality standards based on class II criteria with the lightly polluted category because the IP results show a value of 2.84 which means 1 ≤ IP ≤ 5. Based on the results of data processing of projected population of Padarincang District in the next 10 years amounting to 103,440 people, the total clean water needs of Padarincang District are 149,618,181 m³ / day. It can be concluded that based on the water needs of the Padarincang District Population of 149,618,181 m³ / day with a discharge of 1.2269 m³ / day is said to be unfeasible because the river water discharge < water needs.